PEMBUATAN SIRUP GLUKOSA DARI KULIT PISANG KEPOK (Musa acuminatabalbisianacolla) SECARA ENZIMATIS - Zulqarnain Albaasith, Rahmad Nauli Lubis, Rondang Tambun (Universitas Sumatera Utara, 2014)
Glucose syrup is a trade name of hydrolysis of starch solution. The purpose of this research is to produce glucose syrup from banana peel and examine the variables that affect the hydrolysis process. The process of making glucose syrup in this study through a series of treatment until the resulting slurry is ready to be processed banana peel. Hydrolysis process is then performed using α-amylase and glucoamylase enzyme. This process is carried out in four phases: liquefaction, saccharification, purification and concentration. In the liquefaction process to vary the weight of raw materials: water (10% w / v, 20% w / v, 30% w / v and 40% w / v) and heating temperature (60oC, 70oC, 80oC and 90oC). In this research shows that the best glucose syrup is in the variation of glucose syrup raw materials: water 10% w / v at a temperature of 90oC which produces reducing sugar 9.86% and 98.56% DE value. Keywords : starch, enzyme, glucose syrup